Examining medical doctors’ internship training experience and labour market transition in Kenya - Zhao, Y (2023)
Kenya has a severe shortage of doctors. Despite medical schools increasing the numbers of medical officers (MO) in training, less than half of newly qualified/registered MOs were absorbed by the public sector between 2015 and 2018. It seems timely to understand the labour market for this profession in system terms and in personal terms for doctors, especially during their labour market entry. I used a multiple-method approach including literature reviews, quantitative survey and qualitative interviews to examine doctors’ internship training experiences and labour market transition in Kenya.